Culture learning in a daily space of kitchen: the case of Korean digital kitchen - Jaeuk Park (SpringerOpen, 2021)
Abstract The rapid advancement of technology has allowed computer-assisted language learning (CALL) to have made inroads in the area of pedagogy for language and culture learning. While the majority of studies have used online and virtual environments for culture learning, very little attention has been paid to a real world environment. This study is based on a digital kitchen where students can learn foreign language, culture and cuisine at the same time through cooking tasks. Learning cultural aspects can be properly realised via cooking because the daily activity provides a window into culture, and the digital kitchen provides users with opportunities to directly encounter the target culture themselves via cooking and tasting. 48 international participants conducted two cooking sessions, one in a digital kitchen using real objects and the other in a classroom by looking at typical pictures/photos in a textbook. A range of data sources were employed, such as questionnaires, semi-structured interviews and video-observations to answer the research question. It was found that students learned foreign cultural aspects better when in direct engagement in a digital kitchen by handling actual items than when in a classroom by simply using photos. This study contributes to the development of the real world learning environment for culture learning via innovative technology.